Development of HDPE‐modified eggshell composite. Issue 5 (20th July 2016) - Murugan, Sharmeeni; Munusamy, Yamuna; Muniandy, Mathialagan; Ismail, Hanafi
Abstract : This paper investigates the effects of chemical modification of chicken eggshell powder (ESP) by silane coupling agent on the tensile, morphological, and thermal properties of high density polyethylene/chicken eggshell powder (HDPE/ESP) composites. The tensile and morphological properties of HDPE/ESP composites with and without chemical modifications have been characterized by a light weight tensile tester and scanning electron microscopy (SEM) under different ESP loading. The compounding of composites was done using Rheomix mixture to produce a homogenous mixture of ESP in HDPE. The processing torque is very dependent on the content of HDPE matrix resin. The thermal stability and thermal analysis of the composites were performed by thermogravimetric analysis and differential scanning calorimetric analysis (DSC). DSC result shows no significant differences on the melting and crystallization temperature of HDPE with and without chemical modification of ESP. Tensile strength and thermal stability of HDPE/ESP composites were improved with the modification of ESP by silane coupling agent. FTIR results show that ESP was successfully being modified and the silane coupling agent component is present in the composition. In the presence of silane coupling agent, the interfacial interaction and adhesion between HDPE and ESP were enhanced. POLYM. COMPOS., 39:1630–1637, 2018. © 2016 Society of Plastics Engineers